Frame navigation guided percutaneous balloon compression for intractable trigeminal neuralgia secondary to multiple sclerosis - Jose E. Valerio Pascua; Penelope Mantilla Farfan; Maria Paula Fernandez; Noe Santiago Rea; Matteo Borro; Andres M. Alvarez-Pinzon (Brain and Spine)
Background: Patients with multiple sclerosis (MS) are more likely to develop trigeminal neuralgia (TN) compared to the regular population, due to scarring of the nerve and development of a demyelination plaque. Despite treatment, approximately 10% of MS patients treated for TN experience symptom recurrence, including the development of MS-like symptoms such as optic neuritis and bilateral facial pain. Methods: A computed tomography (CT) scan was performed preoperatively on two patients diagnosed with multiple sclerosis (MS) who experienced secondary trigeminal neuralgia (TN). A precise reference frame was strapped firmly to the patient's forehead during the intraoperative procedure. Preliminary CT images were registered using the navigation system and the bony landmarks were set. Case description: Two patients diagnosed with multiple sclerosis (MS) who experienced refractory trigeminal neuralgia (TN) underwent percutaneous balloon compression. Initial conservative treatment and one dosage of Gamma Knife Radiosurgery (GKR) resulted in symptom control for a few weeks. Both patients had an acute recurrence of pain; thus, percutaneous retrogasserian balloon compression was performed. During follow-up, the patients reported a 70% decrease in pain after the procedure, with minimal recurrence of shooting episodes. Conclusion: Management of trigeminal neuralgia secondary to drug-resistant multiple sclerosis presents a persistent challenge. The percutaneous technique for retrogasserian balloon compression may offer a solution for some patients, but it presents unique challenges for neurosurgeons. Given the complexity of the pathogenesis, target identification, and the potential absence of neurovascular conflict, microvascular decompression remains a debated approach for this patient population. While stereotactic radiosurgery may be a promising alternative.